Copper hexacyanoferrate thin film deposition and its application to a new method for diffusion coefficient measurement - Yun, Jeonghun (2022)
The use of Prussian blue analogues (PBA) materials in electrochemical energy storage and harvesting has gained much interest, necessitating the further clarification of their electrochemical characteristics. However, there is no well-defined technique for manufacturing PBA-based microelectrochemical devices because the PBA film deposition method has not been well studied. In this study, we developed the following deposition method for growing copper hexacyanoferrate (CuHCFe) thin film: copper thin film is immersed into a potassium hexacyanoferrate solution, following which the redox reaction induces the spontaneous deposition of CuHCFe thin film on the copper thin film. The film grown via this method showed compatibility with conventional photolithography processes, and the micropattern of the CuHCFe thin film was successfully defined by a lift-off process. A microelectrochemical device based on the CuHCFe thin film was fabricated via micropatterning, and the sodium ion diffusivity in CuHCFe was measured. The presented thin film deposition method can deposit PBAs on any surface, including insulating substrates, and it can extend the utilization of PBA thin films to various applications.